Passive method-based clusters regulation of two-stage fluidized bed riser using dynamic cluster structure-dependent drag model - Xiaoxue, Jiang; Shuyan, Wang; Baoli, Shao; Marcellus, Ugwuodo U.; Huilin, Lu (Chemical engineering journal (Lausanne, Switzerland : 1996), 2022)
•The criterion distinguishing homogeneous flow from heterogeneous flow is proposed.•A transition regime exists from the first chamber to the second chamber.•Cluster diameter decreases in the contracting-diameter two-stage risers.•Cluster existence time fractions were reduced in diameter-transformed two-stage risers. The passive method-based regulation and control of particle clusters is studied using two-fluid model (TFM) with kinetic theory of granular flow (KTGF) in two-stage fluidized bed risers which include an expanding two-stage riser and contracting two-stage riser. The occurrence of heterogeneous flow with clusters was discriminated using computational threshold in terms of the minimization of energy dissipation rate. The drag coefficient of heterogeneous flow with clusters was simulated using dynamic cluster structure-dependent (DCSD) drag model in a constant-diameter riser and diameter-transformed risers. Comparing to hydrodynamics of gas and particles in a constant-diameter riser, a transition regime exists from the first chamber to the second chamber in the diameter-transformed riser. The solid volume fraction and diameter of clusters decrease in the second chamber. The cluster velocity increased in the contracting-diameter two-stage risers, and decreased in the expanding-diameter two-stage risers. The cluster existence time fractions were reduced in diameter-transformed two-stage risers. Hydrodynamics of clusters are regulated by altering the diameter ratio of the diameter-transformed risers.